An Ayurvedic approach on Pādadāri (Cracked foot). - Rinimol , C E; Vivek , P; Kumar, N Manoj (International Research Journal of Ayurveda & Yoga, 2023)
Cracked Foot referred to as Pādadāri (Cracked foot) in Ayurveda is a common cosmetic foot problem for both men and women. It is reported to be found more in females than in males. The Ayurvedic literature shows that the occurrence of Pādadāri (Cracked foot) can be traced back to ancient times. It is a Vāta (vatha dosha) predominant condition characterized by dry skin, roughness, hardness around the rim of the heel and cracks or fissures on the outer edge of the heel. In persons who are in the habit of too much walking on rough ground without footwear Vāta (vatha dosha) gets increased producing fissures in the sole of feet, this is called Pādadāri (Cracked foot). Cold climate leads to aggravation of Vāta (vatha dosha). This article highlights the importance of Pādābhyaṅga (foot massage with oil) as Dinacarya (daily regimen) aspect by collecting information regarding Pādadāri (Cracked foot) from various classics. In Ayurveda, it is clearly mentioned that Abhyanga (oil massage) controls Vāta dosa(vatha dosha) and the person develops both physical and mental strength.